2013
DOI: 10.1111/kykl.12024
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and Political Instability

Abstract: Summary Immigration may adversely affect political stability if immigrants are perceived unfavourably by host country populations. Using a large sample of countries this study confirms that a higher immigrant share of a population is associated with decrease in the level of political stability. We further demonstrate that a higher immigrant share leads to increased military spending through the channel of political stability. The negative effect of immigration on political stability appears to be stronger in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
(67 reference statements)
2
14
2
1
Order By: Relevance
“…We test whether cultural or genetic closeness (measures suggested by Spolaore and Wacziarg, ), stronger economic relations with geographical neighbors (measured by the intensity of trade), or international migration flows contribute to the impact from neighbors’ political instability on a given country's political instability. While related studies found that immigration and cultural ties with neighbors affect political instability (see Buhaug and Gleditsch ; Gebremedhin and Mavisakalyan, ), our results suggest that the average of neighbors’ population size is the only significant mediating factor between the neighbors’ and a given country's political instability.…”
Section: Introductioncontrasting
confidence: 80%
See 2 more Smart Citations
“…We test whether cultural or genetic closeness (measures suggested by Spolaore and Wacziarg, ), stronger economic relations with geographical neighbors (measured by the intensity of trade), or international migration flows contribute to the impact from neighbors’ political instability on a given country's political instability. While related studies found that immigration and cultural ties with neighbors affect political instability (see Buhaug and Gleditsch ; Gebremedhin and Mavisakalyan, ), our results suggest that the average of neighbors’ population size is the only significant mediating factor between the neighbors’ and a given country's political instability.…”
Section: Introductioncontrasting
confidence: 80%
“…The potential determinants of political instability include economic growth and national income (Alesina and Perotti, ; Feng, ); income inequality (Alesina and Perotti, ; Blanco and Grier, ); democracy and civil liberties (Fearon and Laitin, ; Blanco and Grier; ); government spending (Annett, ); human capital, urbanization share (Alesina and Perotti, ); immigration, openness to trade (Gebremedhin and Mavisakalyan, ); natural resources (Dutt and Mitra, ); population size and population density (Goldstone, ; Buhaug and Gleditsch, ; Gebremedhin and Mavisakalyan, ). The contribution of these time‐varying determinants to political instability is difficult to quantify due to potential reverse causality.…”
Section: The Concept Of Political Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature suggests that migration decisions for poor countries' residents are dependent on both economic causes and noneconomic causes, such as colonial links, family ties, environmental impacts, and political instability. Political instability is significantly reduced by high shares of immigrants, especially in places with assimilative citizenship laws (Gebremedhin & Mavisakalyan, 2013). When a country faces political instability, people from the country are expected to migrate to neighboring countries, thus increasing emigration of the country and decreasing the immigration.…”
Section: Methodology and Datamentioning
confidence: 99%
“…First, it relates to the literature on military budgets, institutions, and conflicts (see, among others, Hoeffler, 2004, 2006;Dunne et al, 2008;Gadea et al, 2004;Yildrim and Sezgin, 2005;Nikolaidou, 2008;Dunning, 2011;Gebremedhin and Mavisakalyan, 2013). Democratic institutions regulate the allocation of power and help to prevent conflicts (see Acemoglu andRobinson, 2006, 2008).…”
Section: Related Literature and Theoretical Considerationsmentioning
confidence: 97%